Numerical simulations of geotechnical engineering problems considering the principal stress rotation - Wang, Zhe (2016)
Soil behaviors are quite complex under dynamic loadings, such as wave loading, earthquake loading, etc, but they share common characteristics that the soil is subjected to considerable principal stress rotations (PSR). PSR can generate plastic deformation even without a change of principal stress magnitudes. Continuous PSR can also generate excess pore water pressures and cumulative shear strains in undrained condition. Therefore, the PSR from the dynamic loadings can accelerate undrained soil liquefaction because it can cause cumulative plastic volumetric deformations. Ignoring PSR induced deformation may lead to unsafe design. It is therefore important to understand the soil behaviors under cyclic loadings with the PSR and take account of this PSR impact in the numerical simulations of corresponding geotechnical problems.